2023
DOI: 10.1186/s13046-023-02616-1
|View full text |Cite
|
Sign up to set email alerts
|

Water channel protein AQP1 in cytoplasm is a critical factor in breast cancer local invasion

Abstract: Background Metastasis of breast cancer grows from the local invasion to the distant colonization. Blocking the local invasion step would be promising for breast cancer treatment. Our present study demonstrated AQP1 was a crucial target in breast cancer local invasion. Methods Mass spectrometry combined with bioinformatics analysis was used to identify AQP1 associated proteins ANXA2 and Rab1b. Co-immunoprecipitation, immunofluorescence assays and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…In this study, AQP1, ITGA5, MAP3K8, PIK3R3, STC1 and TGM2 were significantly overexpressed in HNSCC tumor tissues, while SH2D3C expression was significantly reduced, and there was no difference in ARHGAP4 expression. This is similar to the results of "Guo et al found that AQP1 can promote local invasion of breast cancer, Xu et al found that ITGA5 can promote angiogenesis in cervical cancer, and Lee et al found that MAP3K8 overexpression can induce squamous cell carcinogenesis in the salivary glands of mice" 78 80 . Studies have shown that STC1 is not only one of MRGs, but also a glycolysis-related genes in HNSCC, which is prominently expressed in the glycolytic activities of tumor tissues and can also predict the prognosis of HNSCC from the direction of glycolysis, which is similar to the conclusion of this study 81 .…”
Section: Discussionsupporting
confidence: 84%
“…In this study, AQP1, ITGA5, MAP3K8, PIK3R3, STC1 and TGM2 were significantly overexpressed in HNSCC tumor tissues, while SH2D3C expression was significantly reduced, and there was no difference in ARHGAP4 expression. This is similar to the results of "Guo et al found that AQP1 can promote local invasion of breast cancer, Xu et al found that ITGA5 can promote angiogenesis in cervical cancer, and Lee et al found that MAP3K8 overexpression can induce squamous cell carcinogenesis in the salivary glands of mice" 78 80 . Studies have shown that STC1 is not only one of MRGs, but also a glycolysis-related genes in HNSCC, which is prominently expressed in the glycolytic activities of tumor tissues and can also predict the prognosis of HNSCC from the direction of glycolysis, which is similar to the conclusion of this study 81 .…”
Section: Discussionsupporting
confidence: 84%
“…A western blot assay was used to detect SERPINB5 levels after knockdown and levels of EMT markers. Immunohistochemical (IHC) staining was performed as previously described 18 . IHC was used to test for SERPINB5 protein expression levels in paraffin sections.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical (IHC) staining was performed as previously described. 18 IHC was used to test for SERPINB5 protein expression levels in paraffin sections.…”
Section: Methodsmentioning
confidence: 99%
“…AQP1 induces tumor proliferation and metastasis [46]. Breast cancer tumor cells actively utilize water for angiogenesis and AQP1 plays a vital role in water transport by tumor cells [47]. This study revealed for the first time that leptin regulates the expression of AQP1 at both mRNA (Figure 4B) and protein levels (Figure 4C,D).…”
Section: Discussionmentioning
confidence: 73%